PENANGANAN KELOMPOK RADIKALISME DI WILAYAH KECAMATAN TENGGARONG KABUPATEN KUTAI KARTANEGARA - Putu Ary Suta Wijaya (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractRadicalism is the effort of certain groups, who want a rapid change in society. The group considers the government's legitimate actions to be wrong and only causes suffering for the people so that changes must be made thoroughly even though using violent means. This happened in all parts of Indonesia, one of which was in the Tenggarong Subdistrict of Kutai Kartanegara District. The action was very disturbing for the community. The police at the forefront of law enforcement is expected to be able to handle this act of radicalism. The handling of radical groups in the Tenggarong Subdistrict of Kutai Kartanegara District by the Kutai Kartanegara District Police, by undertaking a cross-sectoral approach strategy in the context of efforts to prevent radicalism and intolerance, namely : (a) Galang and deradicaliation, (b) integrated coordination between Polri, TNI, and Regional Government, (c) monitoring Lapas, (d) monitoring ex-prisoners, (e) em-powering Palmas. The obstacles in handling radical groups in the Tenggarong Subdistrict of Kutai Kartanegara District by the Kutai Kartanegara Police Station and their remedies, namely the community’s indifference to law enforcement so that they do not have effective deterrence to prevent law enforcement that is not in line with a sense of justice that lives within the heart Public. Counteracting radicalism requires synergy between the National Police and the community in efforts to prevent pro-radical and intolerant radicalism carried out by the Kutai Kartanegara District Police by focusing on the function of Bhabinkamtibmas. Keywords : Law Enforcement, Police, Radicalism